비상승 형용사 보문절 구조에 관한 통사적 연구 - 강선옥(Sun-Ok Kang) (언어학 연구, 2011)
In English adjectives can have clauses as their complements. Even though likely and probable are adjectives, there are grammatical differences between them. It is my intention to investigate the structural differences of these adjectives and to show how they relate to complement clauses. Certain sentences used with the word probable are ungrammatical, whereas others with the word likely are grammatically correct. I explain why these differences occur by examining the different complement clauses. First, I show their differences in terms of Government & Binding and then on Phase theory based on a minimalist approach, Chomsky (2000, 2001b). Second, I suggest that probable and likely have different structures: probable selects only CP, whereas likely selects TP and CP. Based on this approach, I have found that with probable it is not possible to raise its subject to the position of the main clause whereas with likely it is possible to raise it to the position of the main clause in complement clauses. Finally, I propose that complement clauses of non-raising adjectives plays a crucial role in accounting for the impossibility of subject-to-subject raising within the complement clauses of non-raising adjectives such as probable. The structure of probable is a strong phase but likely is a weak phase. KCI Citation Count: 0